Mammographic Screening as a Tool for Cardiovascular Risk Assessing. Part 1. Breast Arterial Calcification: Pathomorphology, Prevalence and Risk Factors - E. V. Bochkareva; I. V. Kim; E. K. Butina; I. D. Stulin; S. A. Trukhanov; B. A. Rudenko; S. A. Boytsov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Breast arterial calcification (BAC) is a type of calcification of the media of the middle and small arteries (Menkeberg's calcification). This distinguishes it from calcification associated with the atherosclerotic process and localized in the intima of the vessel. There are data on the association of BAC with cardiovascular diseases (CVD). This allows it to be considered as a new marker of cardiovascular risk in women. The purpose of the first part of the review is to analyze the current literature on the prevalence of BAC, factors related to its occurrence and the association of BAC with traditional CVD risk factors. The prevalence of BAC (data from cancer screening programs) is about 12.7%, and it increases with age to 50% in 80-year-old women. It is not an attribute of "healthy aging", but depends on race and ethnicity. There is a connection with reproductive function. The frequency of BAC increases with the number of children born, with breastfeeding, in menopause, and decreases during hormone replacement therapy. Smoking women have a BAC frequency 2 times less than non-smokers. Detection of BAC on mammograms is associated with conditions pathogenetically associated with CVD: an increase in the frequency of hyperlipidemia, diabetes, chronic kidney disease, a decrease in bone mass. There is a strong correlation of BAC with coronary calcium (indicator of coronary atherosclerosis). A statistically significant association of BAC with overweight, obesity, and smoking was not found, but there is a weak association with arterial hypertension. This may indicate an independent pathophysiological role of BAC in the development of vascular disorders and allows us to consider BAC as an independent marker for improving cardiovascular risk stratification in women. BAC is believed to be a marker of a more generalized trend towards the development of medial calcification in other vascular areas. This leads to a systemic increase in arterial stiffness and contributes to the development of CVD.